2019
DOI: 10.1016/j.whi.2019.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Young Women's Experiences with Coercive and Noncoercive Condom Use Resistance: Examination of an Understudied Sexual Risk Behavior

Abstract: Objectives.-To investigate young women's engagement in and receipt of condom use resistance (attempts to avoid condom use with a partner who wants to use one; CUR), including nonconsensual condom removal ("stealthing"), with male partners. Methods.-Participants were 503 women aged 21-30 with elevated sexual risk characteristics recruited from 2013 to 2017. Participants completed measures assessing sexual victimization history and CUR experiences. Results.-Findings indicated that 87% of women experienced non-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…It appears that our sample may overrepresent individuals with college experience, and be less generalizable to non-students, although this variable was not significant in any analyses. Regarding other limitations, note also that our assessment of stealthing was created for use in this specific study and has not undergone formal psychometric evaluation, though our questions are quite similar to those used in prior research (Davis et al, 2019; Wegner et al, 2018). As with any survey-based research, limitations regarding self-report data arise; however, the use of online versus face-to-face or phone-based methods of administration could reduce concerns regarding anonymity and encourage more accurate self-report.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that our sample may overrepresent individuals with college experience, and be less generalizable to non-students, although this variable was not significant in any analyses. Regarding other limitations, note also that our assessment of stealthing was created for use in this specific study and has not undergone formal psychometric evaluation, though our questions are quite similar to those used in prior research (Davis et al, 2019; Wegner et al, 2018). As with any survey-based research, limitations regarding self-report data arise; however, the use of online versus face-to-face or phone-based methods of administration could reduce concerns regarding anonymity and encourage more accurate self-report.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, among 503 women aged 21-30 years, Davis et al found that 19% of the participants experienced coercive condom use resistance (CUR). Though this does not directly relate to the stealthing behavior promoted on social media, it does shed light on the common practice of sexual acts without condoms when consent is lacking [9].…”
Section: Introductionmentioning
confidence: 95%
“…Leading threats to reproductive autonomy include inability to refuse unwanted sex and low confidence in contraceptive use. Direct threats to contraceptive autonomy include coercive condom negotiation, such as condom use resistance, non-consensual condom removal also known as “stealthing” [ 17 , 18 ] which can prompt unprotected sex as well as fear of future negotiation [ 19 , 20 ]. Reproductive coercion, i.e., partner interference with contraceptive and reproductive decisions, can include direct contraceptive sabotage and enables unintended pregnancy [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%